Vapor deposition silicon-carbon composite material for in-situ growth of interconnected carbon nanotubes and preparation method of vapor deposition silicon-carbon composite material
By growing interconnected carbon nanotubes in situ on new silicon carbon materials, the problem of carbon nanotubes being unable to establish an Internet network is solved, and the conductivity and cycling performance is improved, cost is reduced, and battery life is extended.
Patent Information
- Application Number
- CN202411823547.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, carbon nanotubes cannot establish an Internet network on the surface and inside of new silicon carbon materials, resulting in less obvious improvement in conductivity, and blended carbon nanotubes are costly and easy to fall off, affecting the cyclic performance of the material.
The preparation method of vapor-deposited silicon-carbon composite material for growing interconnected carbon nanotubes in situ, and carbon nanotubes are grown in situ on the surface and inside of silicon-carbon materials using a metal salt catalyst to form a tightly connected interconnect structure.
It significantly improves the conductivity and rate performance of silicon-carbon materials, enhances the structural stability and cycling performance of the materials, reduces production costs, and extends the life of the battery.
Smart Images

Figure CN119650646A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a vapor-deposited silicon-carbon composite material for in-situ growth of interconnected carbon nanotubes and a preparation method thereof. Background Art
[0002] In recent years, with the increasing demand for high energy density batteries, the widely used graphite negative electrode materials have been unable to meet the needs of high specific energy lithium-ion batteries due to their low lithium insertion capacity (theoretical capacity is only 372mAh / g). Silicon-based negative electrode materials have a theoretical specific capacity of up to 4200mAh / g and are becoming the preferred material for the next generation of lithium-ion battery negative electrodes, attracting great attention from academia and industry. However, due to the huge volume effect and the resulting instability of the surface SEI film, silicon-based negative electrode materials are difficult to be actually applied in lithium-ion batteries. This situation restricts the industrial development of high specific energy lithium-ion batteries.
[0003] In 2023, Group 14 of the United States launched a new silicon-carbon composite material with nano-silicon deposited in the micropores of porous carbon, also known as new silicon-carbon. This new silicon-based composite material uses the micropores of porous carbon to accommodate nano- or sub-nano silicon and limit the volume expansion of silicon, thereby reducing the volume effect of the material and effectively solving the problem of ultra-large volume expansion of silicon-based negative electrodes. Due to the reduction of the volume effect, the stability of the SEI film on its surface has also been significantly improved. This new silicon-carbon material not only has a high first coulomb efficiency (about 90%), but also a reversible specific capacity of up to 1800mAh / g, which has received widespread attention from the industry.
[0004] However, this Group 14's new silicon-carbon technology also has some obvious problems and shortcomings. First, the porous carbon skeleton used in this technology is mainly resin-based, biomass-based and petroleum-based porous carbon. Due to the low carbonization temperature, the conductivity of this type of material is very poor, usually more than 2 orders of magnitude lower than that of graphite materials. In addition, the conductivity of nano-silicon is even worse, so the overall conductivity of this composite material is very unsatisfactory, which seriously affects the rate charge and discharge performance of the material. In other words, the battery prepared using this material has poor high current charge and discharge performance and is difficult to meet the high power requirements of the battery. In addition, due to the poor mechanical stability of the porous carbon itself, it is easy to cause the electrode to break during rolling or volume expansion, affecting the long-term cycle performance of the electrode. For this reason, although the cycle performance of this Group 14 new silicon-carbon material is significantly improved compared to the single silicon material, it still cannot meet the needs of long-life batteries. In order to solve these problems, the industry currently generally uses carbon nanotube blending technology to use the ultra-high conductivity of carbon nanotubes to improve the conductivity of silicon-carbon electrodes, and to use the high strength properties of carbon nanotubes to improve the structural stability of new silicon-carbon materials. However, this technical route of blending carbon nanotubes also has many problems and shortcomings. The first is that the carbon nanotubes currently used are expensive, especially single-walled carbon nanotubes, and the amount required for blending is also relatively large, resulting in a very high cost for the actual application of this material. More importantly, the blended carbon nanotubes cannot establish structural connectivity with the new silicon-carbon material and are easily fallen off the surface of the new silicon-carbon, resulting in poor use effect. In addition, the doped carbon nanotubes cannot establish an interconnected network structure on the surface and inside of the new silicon-carbon, and the improvement in the conductivity of the material is not obvious.
[0005] Therefore, how to solve the above technical problems and obtain a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes and a preparation method thereof is a problem that needs to be solved at present. Summary of the invention
[0006] The purpose of the present invention is to provide a vapor-deposited silicon-carbon composite material with in-situ grown interconnected carbon nanotubes and a preparation method thereof, so as to solve the technical problem that carbon nanotubes cannot establish an interconnected network on the surface and inside of new silicon-carbon and cannot effectively improve the conductivity of the material.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a vapor-deposited silicon-carbon composite material for in-situ growth of interconnected carbon nanotubes, comprising the following steps:
[0009] (1) mixing a metal salt with a complexing agent solution, and adjusting the pH of the solution with an alkaline solution to obtain a catalyst precursor solution A;
[0010] (2) mixing the vapor-deposited silicon-carbon composite material with a catalyst precursor solution A, heating and evaporating to dryness to obtain a mixture B;
[0011] (3) subjecting the mixture B to multi-stage heat treatment under air conditions to obtain a mixture C, which is crushed and sieved to obtain a solid powder D;
[0012] (4) In situ growth of carbon nanotubes is carried out on the solid powder D in the presence of a mixed gas of a carbon source gas and a carrier gas, and annealing and cooling are carried out after the introduction of the carbon source gas is stopped, thereby obtaining a vapor-deposited silicon-carbon composite material having in situ grown interconnected carbon nanotubes.
[0013] Furthermore, the metal salt is a metal salt containing one or more of the elements Fe, Co, Ni, Mg, Zn, Cu and Al, and the concentration of the metal salt in the catalyst precursor solution is 0.01 to 2 mol / L.
[0014] Furthermore, the complexing agent solution comprises one or more of itaconic acid solution, mesaconic acid solution, citric acid solution and tartaric acid solution, and the concentration of the complexing agent solution is 0.1-1wt%; the alkaline solution comprises one of ammonia water, ethylenediamine solution, sodium carbonate solution and sodium hydroxide solution, and the pH of the solution is adjusted to between 6 and 9.
[0015] Furthermore, the vapor-deposited silicon-carbon composite material is a composite material in which nano-silicon is deposited in the micropores of porous carbon;
[0016] The mass ratio of the vapor-deposited silicon-carbon composite material to the metal salt is 20-50:0.5-1.5.
[0017] Furthermore, the multi-temperature stage heat treatment is: first heating at 80-150°C for 1-3h; then heating at 180-300°C for 1-3h; and finally heat treatment at 350-500°C for 1-3h.
[0018] Furthermore, the mesh size of the sieving is 100-400 meshes; and the mass ratio of the vapor-deposited silicon-carbon composite material to the catalyst in the mixture C is 95-99.9:0.1-5.
[0019] Furthermore, the volume ratio of the carrier gas to the carbon source gas is 1 to 4:1, the carrier gas comprises nitrogen or argon, and the carbon source gas comprises one or more of ethylene, acetylene, propylene, propyne, butadiene and methane.
[0020] Furthermore, the in-situ growth of the carbon nanotubes is carried out under high temperature reaction, with a heating rate of 5 to 15° C. / min, a reaction temperature of 600 to 900° C., and a reaction time of 0.5 to 2 h.
[0021] Furthermore, the annealing temperature is 600-900° C., the annealing time is 0.5-2 h, and the cooling is natural cooling to room temperature.
[0022] The present invention also provides a vapor-deposited silicon-carbon composite material for in-situ growth of interconnected carbon nanotubes.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention realizes the in-situ growth and interconnection of carbon nanotubes on the surface of new silicon-carbon by using a small amount of catalyst. Different from the route of simply mixing carbon nanotubes, one or more ends of the in-situ grown carbon nanotubes are implanted into the interior or surface of the new silicon-carbon, realizing the effective connection of carbon nanotubes on the surface and internal structure of silicon-carbon, and greatly improving the electronic conductivity of this silicon-carbon material by utilizing the high conductivity of carbon nanotubes themselves. Therefore, the vapor-deposited silicon-carbon composite material prepared by this technology has high rate performance, which can solve the problem of poor rate performance of silicon-carbon materials in the prior art.
[0025] (2) The in-situ grown interconnected carbon nanotubes are firmly bonded to the silicon-carbon material body and will not fall off during pulping and electrochemical cycling. In addition to the high strength of the carbon nanotubes themselves, this in-situ grown interconnected structure helps to improve the mechanical properties of silicon-carbon materials. In particular, it can reduce the volume effect during the material cycle. The composite material has good structural stability, which helps to improve the cycle stability of the vapor-deposited silicon-carbon composite negative electrode material and extend the battery cycle life.
[0026] (3) The preparation method provided by the present invention has simple process, low cost, non-toxicity and harmlessness, and is conducive to large-scale production.
[0027] Therefore, the vapor-deposited silicon-carbon composite material interconnected by in-situ grown carbon nanotubes based on the present invention is an important way to develop high-quality vapor-deposited silicon-carbon composite negative electrode materials, and has clear practical value and development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the SEM image of the original silicon-carbon material of the comparative example;
[0029] Figure 2 This is a SEM image of the vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes prepared in Example 1;
[0030] Figure 3 The first charge and discharge curves of the half-cell prepared from the original silicon-carbon material of the comparative example and the vapor-deposited silicon-carbon composite material of in-situ grown interconnected carbon nanotubes prepared in Example 1;
[0031] Figure 4Comparative Example: Rate performance comparison of half-cells made from original silicon-carbon material and vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes prepared in Example 1;
[0032] Figure 5 The AC impedance spectra of the full battery prepared from the original silicon-carbon material of the comparative example and the vapor-deposited silicon-carbon composite material of in-situ grown interconnected carbon nanotubes prepared in Example 1;
[0033] Figure 6 The first charge and discharge curves of the full battery prepared from the original silicon-carbon material of the comparative example and the vapor-deposited silicon-carbon composite material of in-situ grown interconnected carbon nanotubes prepared in Example 1;
[0034] Figure 7 This is a comparison chart of the long-term cycle performance of a full battery prepared with the original silicon-carbon material of the comparative example and the vapor-deposited silicon-carbon composite material of in-situ grown interconnected carbon nanotubes prepared in Example 1. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a vapor-deposited silicon-carbon composite material for in-situ growth of interconnected carbon nanotubes, comprising the following steps:
[0036] (1) mixing a metal salt with a complexing agent solution, and adjusting the pH of the solution with an alkaline solution to obtain a catalyst precursor solution A;
[0037] (2) mixing the vapor-deposited silicon-carbon composite material with a catalyst precursor solution A, heating and evaporating to dryness to obtain a mixture B;
[0038] (3) subjecting the mixture B to multi-stage heat treatment under air conditions to obtain a mixture C, which is crushed and sieved to obtain a solid powder D;
[0039] (4) In situ growth of carbon nanotubes is carried out on the solid powder D in the presence of a mixed gas of a carbon source gas and a carrier gas, and annealing and cooling are carried out after the introduction of the carbon source gas is stopped, thereby obtaining a vapor-deposited silicon-carbon composite material having in situ grown interconnected carbon nanotubes.
[0040] In the present invention, the metal salt is a metal salt containing one or more of the elements Fe, Co, Ni, Mg, Zn, Cu and Al, preferably one or more of ferric nitrate, nickel nitrate, cobalt nitrate, zinc nitrate, copper nitrate, ferric chloride, cobalt chloride, nickel chloride, zinc chloride, copper chloride, magnesium nitrate and aluminum nitrate.
[0041] In the present invention, the concentration of the metal salt in the catalyst precursor solution is 0.01 to 2 mol / L, preferably 0.05 to 1.5 mol / L, and more preferably 0.08 to 1.2 mol / L.
[0042] In the present invention, the complexing agent solution comprises one or more of itaconic acid solution, mesaconic acid solution, citric acid solution and tartaric acid solution, preferably citric acid solution; the concentration of the complexing agent solution is 0.1-1wt%, preferably 0.2-0.8wt%, and further preferably 0.5-0.6wt%; the alkaline solution comprises one of ammonia water, ethylenediamine solution, sodium carbonate solution and sodium hydroxide solution, preferably ammonia water; the pH of the solution is adjusted to between 6 and 9, preferably 7.
[0043] In the present invention, the molar ratio of the complexing agent to the metal salt in the complexing agent solution is 0.5 to 2:1, more preferably 1 to 1.5:1.
[0044] In the present invention, the vapor-deposited silicon-carbon composite material is a composite material in which nano-silicon is deposited in porous carbon micropores, wherein the deposition amount of silicon is 40-65%, preferably 45-60%, and more preferably 50-55%; the particle size of the vapor-deposited silicon-carbon composite material is 3-15 μm, preferably 5-10 μm, and the specific surface area is less than 5 m 2 / g, the particle size of the vapor deposited silicon-carbon composite material cannot be too large and should be smaller than the diameter of the carbon nanotubes, otherwise the interconnection effect of the carbon nanotubes will be reduced.
[0045] The mass ratio of the vapor-deposited silicon-carbon composite material to the metal salt is 20-50:0.5-1.5, preferably 25-40:0.8-1.2, and more preferably 30-35:1.0.
[0046] In the present invention, the multi-temperature stage heat treatment is: first heating at 80-150°C for 1-3h; then heating at 180-300°C for 1-3h; finally heat treatment at 350-500°C for 1-3h; preferably, first heating at 100-140°C for 2h, then heating at 200-250°C for 2h, and finally heating at 400-450°C for 2h.
[0047] In the present invention, the mesh size of the sieving is 100-400 mesh, preferably 200-300 mesh; the mass ratio of the vapor-deposited silicon-carbon composite material and the catalyst in the mixture C is 95-99.9:0.1-5, preferably 96-99:1-4, and further preferably 97-98:2-3.
[0048] In the present invention, the volume ratio of the carrier gas to the carbon source gas is 1 to 4:1, preferably 2 to 3:1; the carrier gas comprises nitrogen or argon, preferably nitrogen; the carbon source gas comprises one or more of ethylene, acetylene, propylene, propyne, butadiene and methane, preferably ethylene, acetylene or methane.
[0049] In the present invention, the in-situ growth of the carbon nanotubes is carried out under high temperature reaction, with a heating rate of 5 to 15°C / min, preferably 8 to 12°C / min, and more preferably 10°C / min; the reaction temperature is 600 to 900°C, preferably 700 to 800°C, and more preferably 750°C; the reaction time is 0.5 to 2h, preferably 1 to 1.5h.
[0050] In the present invention, the annealing temperature is 600-900°C, preferably 700-800°C, and more preferably 750°C; the annealing time is 0.5-2h, preferably 1-1.5h; and the cooling is natural cooling to room temperature.
[0051] The present invention also provides a vapor-deposited silicon-carbon composite material for in-situ growth of interconnected carbon nanotubes.
[0052] The present invention innovatively develops the technology of in-situ growth of interconnected carbon nanotubes on the surface of silicon-carbon materials. The technology of the present invention realizes the in-situ growth and interconnection of carbon nanotubes on the surface of silicon-carbon materials. One end or multiple ends of the grown carbon nanotubes are implanted on the surface or inside of the new silicon-carbon, forming an effective structural link with the silicon-carbon material, which not only significantly improves the conductivity of the material, but also does not fall off from the surface of the new silicon-carbon during pulping and electrochemical cycling. The high-strength properties of carbon nanotubes also help to improve the mechanical strength and stability of the new silicon-carbon material. Therefore, this in-situ growth of interconnected carbon nanotubes vapor-deposited silicon-carbon composite material and preparation technology can significantly improve the rate performance and cycle stability of vapor-deposited silicon-carbon composite materials, and has important significance and value for the development of high-quality vapor-deposited silicon-carbon composite negative electrode materials.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] Take 0.2g Co(NO3), 0.5g FeCl2 and 0.1g MgCl2 respectively, add 80g of 0.5wt% citric acid solution, stir thoroughly until completely dissolved, then add ammonia water dropwise while stirring, adjust the pH value of the solution to 7, continue stirring for 2 hours, and obtain solution A. Take 50g of vapor-deposited silicon-carbon composite material (silicon deposition amount is 50%) and add it to solution A, stir evenly and heat it to 80℃, continue stirring until the solution is completely volatilized, and obtain mixture B. The obtained mixture B is placed in a high-temperature oven, first dried at 120℃ for 1 hour, then heated to 250℃ and kept warm for 1 hour, and finally heated to 400℃ for heat treatment for 1 hour. 5 g of the treated sample was taken out and crushed through a 200 mesh sieve and then placed in a quartz boat and laid flat. The sample thickness was controlled within 2 mm. The quartz boat was transferred to a tube furnace. The tube furnace was evacuated with a vacuum pump until the vacuum degree was less than 1 Pa. The vacuum pump was turned off and a nitrogen / acetylene (3:1) mixed gas was slowly introduced. The gas intake was 100 mL / min. At the same time, the tube furnace was heated to 700°C at a rate of 10°C / min. The temperature was kept at 700°C for 1 hour and the nitrogen / acetylene (3:1) mixed gas was continued to be introduced. Then the acetylene gas was stopped, and N2 gas was slowly introduced and kept at 650°C for 1 hour. N2 gas was continued to be introduced, and the heating was turned off. After cooling naturally to room temperature, the N2 gas was turned off. The tube furnace was opened and the quartz boat was taken out to obtain a vapor-deposited silicon-carbon composite material interconnected by in-situ growth of carbon nanotubes.
[0056] Scanning electron microscopy and thermogravimetry showed that carbon nanotubes grew on the surface of the vapor-deposited silicon-carbon composite material, with a length of about 10 μm and a diameter of 10 to 20 nm, wherein the carbon nanotubes accounted for 1 to 2% of the total weight of the vapor-deposited silicon-carbon composite material. The composite material prepared above was used to prepare the negative electrode: 1.26 g of the vapor-deposited silicon-carbon composite material interconnected by in-situ growth carbon nanotubes, 0.15 g of conductive carbon black, 0.045 g of sodium carboxymethyl cellulose and 0.044 g of styrene-butadiene rubber were dispersed in 3 mL of deionized water to make a slurry, and then the slurry was coated and dried at 65 ° C for 2 h, pressed and sliced, and then dried in a vacuum drying oven at 120 ° C for 16 h to obtain a vapor-deposited silicon-carbon composite negative electrode. The above negative electrode sheets were assembled into C2032 button batteries in a glove box. After testing, the first charging capacity of the silicon-carbon material with in-situ growth interconnected carbon nanotubes reached 1831.6 mAh / g, and the first coulomb efficiency was 92.7%.
[0057] Example 2
[0058] The difference from Example 1 is that the metal salts used as catalysts are 0.2g Co(NO3), 0.5g Fe(NO3)3 and 0.1g Ni(NO3)2, and the other conditions are the same. The content of carbon nanotubes in the obtained in-situ grown carbon nanotube interconnected silicon-carbon material is 2.1%, the length of the carbon nanotubes is about 10μm, and the diameter is 10 to 20nm.
[0059] Example 3
[0060] The difference from Example 1 is that the metal salts used as catalysts are 0.5g Fe(NO3)3, 0.2g Ni(NO3)2 and 0.1g Cu(NO3)3, and other conditions are the same. The content of carbon nanotubes in the obtained in-situ grown carbon nanotube-interconnected silicon-carbon material is 1.6%, the length of the carbon nanotubes is about 12μm, and the diameter is 10 to 20nm.
[0061] Example 4
[0062] The difference from Example 1 is that the metal salts used as catalysts are 0.6g Fe(NO3)3, 0.2g NiCl2 and 0.1g Zn(NO3)2, and other conditions are the same. The content of carbon nanotubes in the obtained in-situ grown carbon nanotube interconnected silicon-carbon material is 1.9%, the length of the carbon nanotubes is about 10μm, and the diameter is 10 to 20nm.
[0063] Example 5
[0064] The difference from Example 1 is that the complexing agent used is 1% aqueous itaconic acid solution, the dosage is 60g, and other conditions are the same. The content of carbon nanotubes in the obtained in-situ grown carbon nanotube interconnected silicon-carbon material is 2.0%, the length of the carbon nanotubes is about 10μm, and the diameter is 10-20nm.
[0065] Example 6
[0066] The difference from Example 1 is that the alkaline solution used is an aqueous solution of ethylenediamine, the pH value of the metal salt solution is adjusted to 7.0, and other conditions are the same. The content of carbon nanotubes in the obtained in-situ grown carbon nanotube-interconnected silicon-carbon material is 1.9%, the length of the carbon nanotubes is about 10 μm, and the diameter is 10 to 20 nm.
[0067] Example 7
[0068] The difference from Example 1 is that 25 g of porous carbon nano-silicon deposited silicon composite material is added to the solution, so that the weight ratio of the vapor-deposited silicon-carbon composite material to the catalyst is increased to 100:2. Other conditions are the same. The content of carbon nanotubes in the obtained in-situ grown carbon nanotube-interconnected silicon-carbon material is 2.4%, the length of the carbon nanotubes is about 8 μm, and the diameter is 20 to 30 nm.
[0069] Example 8
[0070] The difference from Example 1 is that the ratio of nitrogen / ethylene mixed gas introduced is 2:1, the air intake volume is 80 mL / min, and other conditions are the same. The content of carbon nanotubes in the obtained in-situ grown carbon nanotube-interconnected silicon-carbon material is 2.2%, the length of the carbon nanotubes is about 10 μm, and the diameter is 20 to 25 nm.
[0071] Example 9
[0072] The difference from Example 1 is that the growth temperature of the carbon nanotubes is 800°C, and the carbon nanotubes are kept at this temperature for 1 hour and annealed for 1 hour respectively. Other conditions are the same. The content of carbon nanotubes in the obtained silicon-carbon material interconnected by in-situ grown carbon nanotubes is 1.7%, the length of the carbon nanotubes is about 10 μm, and the diameter is 15 to 25 nm.
[0073] Comparative Example
[0074] The vapor-deposited silicon-carbon composite material (silicon deposition amount of 50%) of Example 1 was directly used to make the negative electrode: 1.26g of vapor-deposited silicon-carbon composite material, 0.15g of conductive carbon black, 0.045g of sodium carboxymethyl cellulose and 0.044g of styrene-butadiene rubber were dispersed in 3mL of deionized water to make a slurry, and then the slurry was coated and dried at 65°C for 2h to obtain a silicon-carbon material electrode, which was pressed and sliced and then dried in a vacuum drying oven at 120°C for 16h to obtain a silicon-carbon material negative electrode. The above silicon-carbon material negative electrode was assembled into a C2032 button half-cell in a glove box.
[0075] Preparation of full battery: In order to be close to production practice, the negative electrode material uses a graphite material mixed with a vapor-deposited silicon-carbon composite material. The mixing amount of the silicon-carbon material is controlled at 10%. The specific capacity of the obtained mixed negative electrode material is 480mAh / g. 3.2 grams of the mixed negative electrode material, 0.05g of conductive carbon black, 0.051g of sodium carboxymethyl cellulose and 0.085g of styrene-butadiene rubber are dispersed in 4mL of deionized water to make a slurry, and then the slurry is coated and dried at 65°C for 2h. The negative electrode sheet is obtained after pressing. The positive electrode material uses NCM811. 2.7g of NCM811 powder, 0.15g of conductive carbon black and 0.15g of PVDF binder are fully dispersed in NMP solvent and coated on an aluminum foil current collector. After drying and pressing, the positive electrode sheet is obtained. The ratio of the surface capacity of the negative electrode material to the surface capacity of the positive electrode material is controlled to be 1.1:1. After slicing and baking the positive and negative electrodes, the full battery is assembled in a glove box. The electrolyte uses 1.0M LiPF6 / (EC+EMC+DEC)(1:1:1)+5%FEC system.
[0076] The electrochemical performance of the half-cells and full-cells prepared in the above Examples 1 to 9 and the comparative examples was tested. All the cells were first charged at 0.05C for 3 cycles, and then charged at 0.2C and discharged at 0.5C for cycle performance testing. The test results are shown in Table 1.
[0077] Table 1 Electrochemical performance test results of C2032 button batteries prepared in Examples 1 to 9 and Comparative Example 1
[0078]
[0079]
[0080] It can be seen from Table 1 that compared with the comparative example, the reversible capacity and first coulomb efficiency of Examples 1-9 obtained by the preparation method of the present invention are improved. The main reason for this performance improvement is attributed to the interconnected structure formed by the in-situ grown carbon nanotubes on the surface and inside of the silicon-carbon material. In addition, the cycle performance of the full battery prepared using this material is more significantly improved. Compared with the comparative example, the full battery prepared using Examples 1-9 has a capacity retention rate of about 10 percentage points after 500 cycles, which greatly extends the life of the battery. The reason is due to the stabilizing effect of the in-situ grown carbon nanotubes on the silicon negative electrode, including the high-strength carbon nanotubes reducing the volume effect of silicon-carbon, and the long-range conductivity of the carbon nanotubes so that the broken silicon-carbon will not lose its conductive activity. It can be seen that the present invention can significantly improve the various electrochemical properties of silicon-carbon materials and improve the cycle stability through the in-situ grown carbon nanotubes interconnected silicon-carbon materials, which is an important way to develop high-performance silicon-carbon negative electrode materials.
[0081] contrast Figure 1 and Figure 2 It was found that the carbon nanotubes prepared in Example 1 were tightly connected to the surface of the silicon-carbon material and even penetrated deep into the interior, forming an interconnected structure of the surface and the bulk phase. The grown carbon nanotubes would not fall off the surface of the silicon-carbon and were more effective in improving the conductivity and stability of the inner core.
[0082] contrast Figure 3 It was found that compared with the comparative example, when the in-situ grown carbon nanotube interconnected silicon-carbon material prepared in Example 1 was used as the negative electrode of a lithium-ion battery, the reversible capacity of the material reached 1851.6 mAh / g, which was higher than 1790.4 mAh / g of the comparative sample. Moreover, the first coulombic efficiency of the material prepared in Example 1 reached 92.7%, which was significantly higher than 88.1% of the comparative sample.
[0083] contrast Figure 4It is found that compared with the comparative example, the rate performance of the in-situ grown carbon nanotube interconnected silicon-carbon material prepared in Example 1 is significantly improved. At a discharge rate of 10C, when the comparative sample has almost no capacity, Example 1 still has a reversible capacity of nearly 1000 mAh / g. This shows that the in-situ grown carbon nanotube interconnected structure of the present invention significantly improves the power properties of the vapor-deposited silicon-carbon composite material.
[0084] Figure 5 The AC impedance spectra of the half-cells assembled for the comparison sample and Example 1 are shown. Compared with the comparative example, the impedance of the half-cell prepared in Example 1 is significantly lower than that of the comparative example. This low impedance property is related to the in-situ growth of carbon nanotubes that improves the conductivity of the material, which also explains the reason for the high rate performance of Example 1.
[0085] contrast Figure 6 The performance of the full battery prepared after mixing with graphite showed that, compared with the comparative example, the first coulombic efficiency and reversible capacity of the full battery of silicon-carbon material interconnected by in-situ grown carbon nanotubes prepared in Example 1 were also slightly improved. Although not particularly obvious, it also showed some advantages.
[0086] Figure 7 It can be seen that compared with the comparative example, the cycle performance of the full battery of silicon-carbon material interconnected by in-situ grown carbon nanotubes prepared in Example 1 is significantly improved. After 500 cycles, the capacity retention rate of the full battery prepared by the material of Example 1 is 10 percentage points higher than that of the comparative sample, which significantly extends the life of the battery. This illustrates the advantages of vapor-deposited silicon-carbon composite materials interconnected by in-situ grown carbon nanotubes in practical applications.
[0087] As can be seen from the above embodiments, the present invention provides a vapor-deposited silicon-carbon composite material interconnected by in-situ growth of carbon nanotubes and a preparation method thereof. The present invention firstly treats a metal salt catalyst solution after complexation and neutralization, and then blends it with a silicon-carbon material, places the catalyst on the surface and inside of the silicon-carbon material, and in-situ grows carbon nanotubes under appropriate conditions to obtain a vapor-deposited silicon-carbon composite negative electrode material interconnected by in-situ growth of carbon nanotubes. One or more ends of the carbon nanotubes are rooted in the surface or inside of the silicon-carbon material. Based on its strong electrical conductivity, the problem of low electrical conductivity of the vapor-deposited silicon-carbon composite material can be solved. At the same time, based on the high strength of the carbon nanotubes, the volume effect of the composite material can be reduced, the volume expansion of the negative electrode material is limited, and the life of the battery is significantly extended.
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a vapor-deposited silicon-carbon composite material for in-situ growth of interconnected carbon nanotubes, characterized in that: The following steps are involved: (1) mixing a metal salt with a complexing agent solution, and adjusting the pH of the solution with an alkaline solution to obtain a catalyst precursor solution A; (2) mixing the vapor-deposited silicon-carbon composite material with a catalyst precursor solution A, heating and evaporating to dryness to obtain a mixture B; (3) subjecting the mixture B to multi-stage heat treatment under air conditions to obtain a mixture C, which is crushed and sieved to obtain a solid powder D; (4) In situ growth of carbon nanotubes is carried out on the solid powder D in the presence of a mixed gas of a carbon source gas and a carrier gas, and annealing and cooling are carried out after the introduction of the carbon source gas is stopped, thereby obtaining a vapor-deposited silicon-carbon composite material having in situ grown interconnected carbon nanotubes.
2. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 1, characterized in that: The metal salt is a metal salt containing one or more of the elements Fe, Co, Ni, Mg, Zn, Cu and Al, and the concentration of the metal salt in the catalyst precursor solution is 0.01-2 mol / L.
3. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 1 or 2, characterized in that: The complexing agent solution comprises one or more of itaconic acid solution, mesaconic acid solution, citric acid solution and tartaric acid solution, and the concentration of the complexing agent solution is 0.1-1wt%; the alkaline solution comprises one of ammonia water, ethylenediamine solution, sodium carbonate solution and sodium hydroxide solution, and the pH of the solution is adjusted to between 6 and 9.
4. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 3, characterized in that: The vapor-deposited silicon-carbon composite material is a composite material in which nano-silicon is deposited in the micropores of porous carbon; The mass ratio of the vapor-deposited silicon-carbon composite material to the metal salt is 20-50:0.5-1.
5.
5. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 1 or 4, characterized in that: The multi-temperature stage heat treatment is: firstly heating at 80-150°C for 1-3h; then heating at 180-300°C for 1-3h; and finally heat treating at 350-500°C for 1-3h.
6. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 1, 2 or 4, characterized in that: The mesh size of the sieving is 100-400 meshes; the mass ratio of the vapor-deposited silicon-carbon composite material to the catalyst in the mixture C is 95-99.9:0.1-5.
7. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 6, characterized in that: The volume ratio of the carrier gas to the carbon source gas is 1 to 4:1, the carrier gas comprises nitrogen or argon, and the carbon source gas comprises one or more of ethylene, acetylene, propylene, propyne, butadiene and methane.
8. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 1, 4 or 7, characterized in that: The in-situ growth of the carbon nanotubes is carried out under high temperature reaction, with a heating rate of 5 to 15° C. / min, a reaction temperature of 600 to 900° C., and a reaction time of 0.5 to 2 hours.
9. The method for preparing a vapor-deposited silicon-carbon composite material with in-situ growth of interconnected carbon nanotubes according to claim 1, characterized in that: The annealing temperature is 600-900° C., the annealing time is 0.5-2 h, and the cooling is natural cooling to room temperature.
10. A vapor-deposited silicon-carbon composite material of in-situ grown interconnected carbon nanotubes prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Method for improving structural stability of silicon carbon material
CN122126853A
Organic-inorganic double-doped silicon-carbon negative electrode material, preparation method and application
CN122494606A
An assembled irregular polyhedral carbon matrix and a preparation method thereof
CN122677441A